Pertanggungjawaban Pidana bagi Pelaku Tindak Pidana Turut Serta Melakukan Pembunuhan di Kabupaten Ende - Vinsensius Rau; Karolus K. Medan; Aksi Sinurat (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Criminal liability is a form of imposing punishment on the perpetrator of a crime because of his/her unlawful actions. In other words, criminal liability determines whether a person will be acquitted or convicted of a crime that has been committed. This process involves the transfer of the existing punishment for the crime to the perpetrator. This research is a normative research. The results of the research show that Criminal liability for perpetrators who participate in the crime of murder, anyone who intentionally helps, plans, or plays an active role in murder can be held criminally responsible, either as the main perpetrator or as a participant (medeplichtige or medepleger). The sanctions imposed depend on the role and level of involvement of each perpetrator, in accordance with the principle of criminal responsibility and the element of error in criminal law. This must be reviewed carefully by the judge so that in making a decision on the defendant, it can have a deterrent effect on the perpetrator and not cause unrest for the victim's family regarding the decision handed down by the judge. The judge's decision to impose a light sentence on the perpetrator who participated in a crime that resulted in the death of a person shows an imbalance in law enforcement. This injustice can be caused by the judge's non-objective considerations, weak evidence, or lack of bias towards justice for the victim. This kind of decision risks weakening the deterrent effect and public trust in the justice system.